Cranial ultrasound as a complementary method to the general movements assessment in preterm infants for predicting the neurological outcome - a single center experience - Zlatanović Dragan; Čolović Hristina; Živković Vesna; Stanković Anita; Kostić Milica; Pejčić Vuk; Radovanović Vukota (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. Implementing cranial ultrasound (CUS) into daily clinical practice represents a major advance in the diagnosis and treatment of newborns. Preterm birth is considered a risk factor for abnormal neurological development. The study aimed to evaluate the significance of CUS in preterm infants as a complementary method to the General Movements Assessment for predicting neurological outcomes. The study focused on a cohort of infants without significant neonatal morbidity. Methods. The study included 160 preterm infants and was designed as a prospective clinical study. Statistical analysis included cranial ultrasound findings and the assessment of spontaneous motor activity in the first five days after birth (“Writhing” period), perinatal data, and pregnancy data. Results. There was a statistically significant association between abnormal CUS findings and cerebral palsy in the final neurological outcome (p < 0.001). Pathological CUS findings were significantly more frequent in preterm infants born before 30 weeks of gestation (p < 0.001), those delivered by cesarean section (p < 0.001), and infants with an Apgar score < 8 at one and five minutes (p < 0.001). The specificity of a normal CUS was 86% but increased to 100% when combined with a normal General Movements Assessment. Conclusion. This research confirms that CUS can be a valuable tool for predicting neurological outcomes in preterm infants. It can provide data that can guide the judicious use of different monitoring methods and rationalize their examinations.